Effect of an Interactive Training on Choosing Delivery Method among Primiparous Pregnant Women: An Interventional Study - Zarifsanaiey, Nahid; Bagheri, Alireza; Jahanpour, Faezeh; Nematollahi, Samaneh; Azodi, Parviz (Investigación y Educación en Enfermería, 2020)
Objective. To evaluate the effect of interactive training conducted during pregnancy on choosing delivery method among primiparous women. Methods. Quasi-experimental study carried out in 2017 in two hospitals in the city of Bushehr (Iran), with the participation of 108 primiparous pregnant women in an educational program consisting of eight 2-hour sessions every two weeks in which interactive training activities were performed (group discussions, classroom sessions, and delivery of printed educational material) on themes related with physiological delivery, painless vaginal delivery methods, and complications of cesarean delivery without indication, among others. Before and after the intervention, the Knowledge and Preferred Method of Delivery Questionnaire by Moradabadi et al., was used to obtain information. Results. The results indicated that the level of knowledge in the group of mothers increased significantly between the pre-intervention and post-intervention assessment (13.2 versus 19.4, of 20 possible maximum points; p <0.001). Additionally, significant difference was observed in the selection of the vaginal delivery method before and after the intervention (74.1% versus 98.1%; p<0.001). Conclusion. Implementation of interactive training increased knowledge of pregnant women on the delivery and induced a positive effect to encourage the primiparous mothers to have a vaginal delivery. How to cite this article: Zarifsanaiey N, Bagheri A, Jahanpour F, Nematollahi S, Azodi P. Effect of an Interactive Training on Choosing Delivery Method among Primiparous Pregnant Women: An Interventional Study. Invest. Educ. Enferm. 2020; 38(1):e04.